Dionysos and His Retinue in the Art of Late Roman and Byzantine Palestine - Rosenthal-Heginbottom, Renate (Actual Problems of Theory and History of Art, 2015)
Dionysian imagery was a popular subject in the visual arts of ancient Palestine, reflecting a Hellenistic cultural heritage no longer identified with paganism. Dionysus’ popularity, universality, and longevity are due to the convivial aspect of wine-consuming among the Greeks: the idea of sharing. Scenes and motifs embellish different items: mosaic floors, sculpture and carved stone; marble and stone sarcophagi and lead coffins; tableware, household vessels, metal and clay lamps; bronze and clay figurines; ivory and bone carvings; textiles; coins; jewelry. The contextual evidence indicates that pagans, Jews and Christians made use of the same iconography.
Keywords: cult of Dionysus; late Roman and Byzantine Palestine; villa furnishings; symposium; social elite; paganism; Judaism; Christianity